Evaluation of nutrition in children of preschool age - Suliga, Edyta; Cieśla, Elżbieta; Zemlik, Joanna; Pietraszkiewicz, Magdalena Joanna (Journal of Education, Health and Sport, 2017)
Introduction. Overweight and obesity resulting in preschool are difficult to reverse, and are associated with many serious health complications and increased risk of premature illness and death in adulthood. Few of the existing publication evaluates daily food rations preschool children. Aim of the study. Evaluation of nutrition of children of preschool age in terms of demand for energy and macronutrient intake in children of normal BMI and overweight children and obesity. Material and methods.The analysis included 102 children. Nutritional status was assessed on the basis of anthropometric characteristics and indicators in relation to the WHO centile charts. Feeding analyzed on the basis of average daily intake, calculated as the mean of the 3-day storage menus. Estimation of the nutrient content in the children’s diet was carried out using diet 5. The analysis used statistical package STATISTICA 12.0. Results. BMI correct in 83% of subjects, and 16% of excess body weight were observed. With regard to the energy and nutritional average daily food rations showed no statistically significant differences between the group of children with normal BMI and a group of children with overweight and obesity. The supply of energy and macronutrients in average daily diet of children deviated from the recommended standards among both groups of children studied. Conclusions.The results showed a number of deficiencies in the nutrition of preschool children. Intake of nutrients in daily food rations differ from dietary recommendations for this age group. It is necessary to educate parents on the proper nutrition of children.